THE FORMATION OF PSYCHOLOGY AS A SCIENCE IN THE MIDDLE AGES - Oqnazarova Mavluda Nurboyevna (Western European Studies, 2025)
This article analyzes the process of the formation of psychological knowledge as an independent scientific direction in the Middle Ages based on a historical-philosophical approach. In particular, the views of Eastern thinkers on the human psyche, mental activity and moral qualities, their contribution to the development of the science of psychology are highlighted. The expression of psychological ideas in the works of such scientists as Abu Nasr Al-Farabi, Ibn Sina, and Jalaluddin Davani and their influence on modern psychology are scientifically analyzed. Also, the development paths of psychology in Western Europe and the Islamic world are compared and their specific aspects are highlighted
Keywords: history of psychology; Middle Ages; Eastern thinkers